2008
DOI: 10.1111/j.1365-2958.2008.06172.x
|View full text |Cite
|
Sign up to set email alerts
|

Small non‐coding RNAs in Caulobacter crescentus

Abstract: SummarySmall non-coding RNAs (sRNAs) are active in many bacterial cell functions, including regulation of the cell's response to environmental challenges. We describe the identification of 27 novel Caulobacter crescentus sRNAs by analysis of RNA expression levels assayed using a tiled Caulobacter microarray and a protocol optimized for detection of sRNAs. The principal analysis method involved identification of sets of adjacent probes with unusually high correlation between the individual intergenic probes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 52 publications
1
102
0
4
Order By: Relevance
“…As an additional control, we observed that CckA did not coimmunoprecipitate with Hfq-M2, an abundant RNA-binding protein (22), demonstrating that the coimmunoprecipitation of CckA with DivL-M2 is specific. Taken together, these results suggest that DivL promotes the autophosphorylation and activation of CckA, directly or indirectly, by localizing CckA and DivL at the new cell pole in the same protein complex.…”
Section: Divl Promotes Ccka Activation By Localization Of Ccka and DImentioning
confidence: 83%
“…As an additional control, we observed that CckA did not coimmunoprecipitate with Hfq-M2, an abundant RNA-binding protein (22), demonstrating that the coimmunoprecipitation of CckA with DivL-M2 is specific. Taken together, these results suggest that DivL promotes the autophosphorylation and activation of CckA, directly or indirectly, by localizing CckA and DivL at the new cell pole in the same protein complex.…”
Section: Divl Promotes Ccka Activation By Localization Of Ccka and DImentioning
confidence: 83%
“…Some of the genes involved in the increased resistance to stresses at this phase are regulated by extracytoplasmic function (ECF)-type sigma factors, such as some oxidative stress genes that are regulated by the extracytoplasmic sigma factor SigF (1). Moreover, several small regulatory RNAs are induced at stationary phase and by nutrient starvation, suggesting that the regulatory network controlling gene expression at this phase may be more complex than one relying on a single master regulator (30).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the potential involvement of sRNAs in inactivating transposition in bacteria (Landt et al 2008). The role of sRNAs regulation of transposition in E. coli was illustrated in an elegant study by Ross et al (2010).…”
Section: Involvement Of Srnas In Mycobacterial Growth Metabolism Anmentioning
confidence: 99%